The Amidolytic Activity of the SK-Plasminogen Complex Is Enhanced by a Potentiator which Is Generated in the Presence of Vascular Plasminogen Activator - Role of Fibrin Degradation Products - Soria, J; Soria, C; Bertrand, O; Dunn, F; Samama, M; Bachmann, F (Thrombosis and Haemostasis, 1982)
In the presence of an excess of streptokinase (SK) the amidolytic activity of the plasminogen-SK complex on chromogenic substrates is 12% lower in serum than in the corresponding plasma. However, in subjects in whom venous stasis lead to a shortening of the euglobulin lysis time to less than 60 min (high responders), the amidolytic activity of the plasminogen-SK complex in serum was 60% higher than in the corresponding plasma. Attempts to find alterations of the plasminogen molecule itself which would account for the enhanced activity in high responder serum were negative. No free plasmin was present and the plasminogens isolated from plasma and serum before and after venous stasis had the same amidolytic activity as glu-plasminogen in the presence of an excess of SK. N-terminal analysis of these four plasminogens revealed in each instance glutamic acid.The enhancement of the amidolytic activity of the SK-plasminogen complex in serum of high responders (potentiator activity) could be reproduced by adding purified tissue plasminogen activator (TA) to native blood before clotting, but not if TA was added to plasma or to prestasis serum. Removal of fibrin degradation products from poststasis serum resulted in the disappearance of potentiator activity. These experiments suggest that fibrin degradation products, generated during clotting in the presence of vascular or tissular plasminogen activator act as a potentiator of the amidolytic activity of the plasminogen SK-complex.
Keywords: Plasminogen; SK-plasminogen complex; Fibrinolysis; Potentiator of SK-plasminogen complex; Tissue plasminogen activator; Venous stasis test; Fibrin degradation products